2012
DOI: 10.1093/nar/gks167
|View full text |Cite
|
Sign up to set email alerts
|

The asparagine-transamidosome from Helicobacter pylori : a dual-kinetic mode in non-discriminating aspartyl-tRNA synthetase safeguards the genetic code

Abstract: Helicobacter pylori catalyzes Asn-tRNAAsn formation by use of the indirect pathway that involves charging of Asp onto tRNAAsn by a non-discriminating aspartyl-tRNA synthetase (ND-AspRS), followed by conversion of the mischarged Asp into Asn by the GatCAB amidotransferase. We show that the partners of asparaginylation assemble into a dynamic Asn-transamidosome, which uses a different strategy than the Gln-transamidosome to prevent the release of the mischarged aminoacyl-tRNA intermediate. The complex is describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 51 publications
5
21
0
Order By: Relevance
“…The K m value of GatCAB wt for Asp-tRNA Asn (1.67 mM) resembles that of H. pylori GatCAB (1.12 mM) for Asp-tRNA Asn (Fig. 4, Table 1) (Fischer et al, 2012).…”
Section: Overproduction and Purification Of M Catarrhalis Gatcabsmentioning
confidence: 63%
“…The K m value of GatCAB wt for Asp-tRNA Asn (1.67 mM) resembles that of H. pylori GatCAB (1.12 mM) for Asp-tRNA Asn (Fig. 4, Table 1) (Fischer et al, 2012).…”
Section: Overproduction and Purification Of M Catarrhalis Gatcabsmentioning
confidence: 63%
“…(ii) The Gln and Asn transamidosomes in Helicobacter pylori are transiently formed in the presence of tRNA Gln and tRNA Asn , respectively (32,33). A protein component Hp0100 can facilitate the formation of a stable Asn transamidosome in H. pylori (34).…”
Section: Discussionmentioning
confidence: 99%
“…AdT, ND-AspRS, and Hp0100, a Protein of Unknown Function-In contrast to the stable, tRNAdependent Asn-transamidosome from T. thermophilus, an analogous H. pylori Asn-transamidosome could not be isolated (15). We investigated the possibility that a protein of unknown function is needed to promote assembly of a more stable complex.…”
Section: Published Yeast Two-hybrid Results Suggest Biologically Signmentioning
confidence: 99%
“…1C, lane 5) (15). We recently showed that the H. pylori Asn-transamidosome is dynamic and unstable (15).…”
Section: Hp0100 Adt and Nd-asprs Assemble Into Binary And Ternary Cmentioning
confidence: 94%
See 1 more Smart Citation